EVALUATION OF THE RELATIONSHIP BETWEEN BRUXISM INDEX AND PERSONALITY TRAITS - Steliana Gabriela Buștiuc; Raluca Briceag; Elena Claudia Sin; Gheorghe Raftu; Mihaela Macrina Manolache; Salim Camer; Cristina Nucă; Aureliana Caraiane (Romanian Journal of Medical and Dental Education)
Personality traits play an important role in diagnosis and treatment, and physical health should not be managed without due consideration of psychological needs. There are a number of studies that have investigated the link between personality traits and bruxism. The aim of this study is to highlight the relationship between the bruxism index and personality traits in a group of patients with defined sleep bruxism (SB). Material and methods: This study is a cross-sectional study. It used the identification of the bruxism index (BI) recorded during sleep using the Bruxoff device. The 5-Factor Personality Questionnaire (CP5F) was used to assess personality traits. The questionnaire contains a number of 130 items that are concentrated in six scales. Each item presents five response options. Results: The study included a number of 40 female and male patients diagnosed with definite bruxism aged between 22 and 56 years. The mean value of the bruxism index recorded during sleep was 6.160±2.474. The Pearson correlation coefficient revealed statistically significant values ​​between the bruxism index variable and the variables represented by the scores obtained for extraversion, conscientiousness and emotional stability. Conclusion The bruxism index showed a strongly-negative significant correlation with extraversion and emotional stability and a moderate positive and statistically significant relationship between the bruxism index variable and the rated scores (T) for conscientiousness. These findings could lead to a specific prevention plan for these personality traits through a multidisciplinary approach (dentist – psychologist), which, in addition to positively influencing aspects related to diagnosis and treatment, can lead to a holistic understanding of the patient.